Are surrounding patches barriers for Prays oleae (Bernard) in the olive agroecosystem? - Villa, María (2017)
The increasing interest in organic products leads to a need of finding strategies for pest control free of pesticides. Conservation biological control, through habitat management, seeks to manage the environment in order to achieve pest reductions. In this context, the surrounding habitats of agroecosystems can be management in order to impede pest dispersion and for that is crucial to understand how landscape connectivity affects pest’s species. Thus, we studied the capability of Prays oleae (Bernard) to disperse through non-crop patches composed by woody and herbaceous vegetation. For that the flight activity of P. oleae was monitored in olive groves, and surrounding scrubland and herbaceous patches from the end of March to December of 2012 and 2013. Generalized Linear Models were used to analyze the abundance of P. oleae in the different patches and locations. P. oleae captures varied between years, likely because of a strong relation with the weather conditions. For the first time, landscape connectivity aspects were identified for P. oleae, being that was clearly able to disperse over scrublands and herbaceous patches. This study provides new data that contributes to the knowledge about P. oleae dynamic under adverse weather conditions and discloses new queries about the P. oleae dispersion and movement between patches.